Attachment and parental reflective functioning features in ADHD: enhancing the knowledge on parenting characteristics - Cavallina, Clarissa; Pazzagli, Chiara; Ghiglieri, Veronica; Mazzeschi, Claudia (Frontiers in Psychology, 2015)
Attention-deficit/hyperactivity disorder (ADHD) is a disorder characterized by a chronic, pervasive, and developmentally inappropriate level of impulsivity, attention and concentration. It is associated with adverse academic and social functions and stress to families. Studies provide evidence that family variables are correlated with this disorder and that parenting styles play an important role in its complexity. However, a thorough investigation of the impact of parental affective and relational aspects on the ADHD child’s areas of functioning is still needed. We suggest investigating parenting characteristics to a greater extent by adopting an attachment perspective with a focus on parental reflective functioning as it pertains to the child’s ADHD clinical condition. In future research, parents’ attachment and the parental reflective functioning should be taken into account.